Kajian Warna dan Motif Kain Tenun Upcycle pada Produk CV. Tarum Bali - Ni Luh Ayu Pradnyani Utami (Pascasarjana ISBI Bandung, 2018)
Upcycle woven fabric is an innovation product applying upcycling concept produced by CV Tarum Bali. The eminence of this product is the using of natural dye which increases the selling value. This is interesting to be studied because of the uniqueness of color and motif of the product. The method applied in this study is qualitative. The samples are determined based on purposive sampling, while the data are collected from observation, interview, and documentation. The result shows that the natural dyes used for the upcycle are as follows: the leaves of mahogany tree for brown color; blackfrom the leaves of ketapang tree; yellow from the leaves of mango tree; red from the log of secang tree; indigo or blue from the leaves of tarum. The colors usually applied for upcycle woven fabric tend to be lightcolor which is not easily faded. The motif of the upcycle is usually the order of horizontal lines. The motif emerges from the crossing between lungsi yarn and rag strings. The motif arrangement of the upcycle is either the repetition of form, direction, sixe, or color which considers the composition, balance, and rythm. The motif of horizontal lines is compounded by the repetition of rythm and transition to reach formal balance. It results in motif design which is harmonious and united.Keywords: Color, motif, woven fabric, upcycle, CV Tarum Bali